Ethical and existential challenges associated with a cancer diagnosis. Issue 5 (3rd May 2010) - Pascal, Jan; Endacott, Ruth
Abstract : Background: At the point of cancer diagnosis, practitioners may wrestle with ethical dilemmas associated with medico-legal implications of diagnosis, treatment options and disclosure to family members. The patient's perspective can take a different route, focusing on ethical and existential questions about the value and purpose of life, culminating in the question: how do I lead my life after diagnosis? Objective: To explore the ethical and existential challenges associated with a cancer diagnosis from the perspective of cancer survivors. Design: Qualitative design using specifically phenomenological methods to enable focus on subjective experience. Two in-depth interviews were conducted over a 6-month period. Setting: Bendigo, Victoria, Australia. Participants: 15 participants (n=11 women and n=4 men) volunteered to be interviewed. Age ranged from 32 to 85 years of age; length of survival 0.5–25 years; with a range of cancer diagnoses. Results: Findings demonstrated that participants experienced existential and ethical challenges associated with a cancer diagnosis and subsequent survivorhood. These challenges were present regardless of cancer stage or diagnostic type and pervaded throughout length of survival. The existential challenges included the experience of anxiety and uncertainty about recurrence and metastatic disease. In particular, participants reported iatrogenic uncertainty induced by tests and treatment with follow-up regimes underscoring the fragility of survivor status. Uncertainty served as a 'wake-up call' and precipitated ethical challenges. Such challenges involved making meaning of survivorhood and questioning of morals, values and relationships. At times these questions were painful and difficult, creating unease about leading a 'good' and purposeful life. Entering ethically rocky terrain was also considered identity enhancing, with reports that a cancer diagnosis could have benefits as well as challenges. Conclusion: This study identified a number of challenges associated with a cancer diagnosis; these have implications for the preparation of medical, nursing and social work practitioners and should be considered during the design of follow-up support for cancer patients and those in recovery.